The Ministry of Trade and Industry Decree No. 993 of the Year 2010 Concerning The Organic Products = وزارة التجارة والصناعة قرار رقم 993 لسنة 2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.